Biogeographic patterns of endolithic cyanobacteria and their negative impacts on mussels along the South African coast - Ndhlovu, Aldwin (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2020)
Endolithic cyanobacterial species occur in a wide range of environments including cold and hot deserts as well as marine systems where they attack biological material such as corals and the shells of molluscs including limpets, mussels and abalone. Endoliths live as parasites in mussel shells, where they erode and extract calcium carbonate leading to shell weakening, creating fracture holes that lead to shell collapse and death, but they also have positive effects when they lead to discolouration of mussel shells hence giving them the ability to reduce stressful heat gain during periods of extreme heat stress. Mussels are ecological engineers on which the abundance and diversity of associated species assemblages depend. Understanding how endolithic cyanobacteria affect mussels will not only help in predicting future patterns of mussel abundances, but also future patterns of the infauna that depend on them. Firstly, I identified endolithic species infesting mussels and assessed the prevalence of endolithic parasitism in two intertidal mussel species in South Africa, the native Perna perna and the invasive Mytilus galloprovincialis. Large-scale surveys of endolithic infestation of mussels were conducted along 2500 km of the South African coast, covering three biogeographic regions: the subtropical east coast, dominated by P. perna, the warm temperate south coast where the indigenous species coexists with M. galloprovincialis, and the cool temperate west coast which is dominated by M. galloprovincialis. The prevalence of endolithic infestation was higher in the cool temperate bioregion than in the warm temperate and subtropical bioregions which did not differ and for P. perna endolithic species assemblages revealed clear groupings by bioregion. Results for endolithic induced mortality followed the same trend, with no significant difference between the two mussel species where they coexist and these results attribute biogeography of endoliths to environmental factors rather than host identity. Secondly, I assessed energy budgets of infested and clean mussels, to evaluate the energetic cost of infestation. This involved measuring energy acquisition, expenditure, calculating scope for growth and lethal temperatures (LT50s). The results revealed that endolithic cyanobacteria have a negative effect on scope for growth due to increased metabolic rates for infested mussels, with no effect of endoliths on the rates or efficiency of energy acquisition through filtration and no effect on lethal temperatures. The effects of infestation were then examined in more detail through a qualitative and quantitative analysis of mussel gonads and byssal attachment strength to the substratum. Endolithic infestation was found to affect reproduction by affecting the size (mass) of gonads, but not the density of eggs within them. Attachment strength was affected by endolithic infestation with very infested mussels requiring much less force to detach them from the substratum compared to mussels with low or no infestation. These results show that endolithic infestation affects mussel fitness by directly affecting attachment strength and by reducing their reproductive output. Thirdly, endolithic succession within mussel shells was examined by assessing endolithic species composition in different regions of the shell and as a function of time. The results on the spatial distribution of endolith species within a shell supported those for temporal succession in shells deployed in the field. Endolithic species that were early colonists of clean shells were similar to those that were found in the distal edge, the new and growing region of the shell and species that arrived late in succession were similar to endolithic species found near the umbo, the oldest region of the shell. Overall, the study shows that endolithic cyanobacteria show the effects of biogeography on species distribution and clear patterns of succession within mussel shells. Cyanobacteria affect mussels negatively; they lead to low scope for growth and hence low growth rates, low reproductive output and reduced attachment strength for infested mussels. This, in turn is expected to have indirect consequences for other species that rely on mussels as ecological engineers for their survival.
Keywords: Cyanobacteria -- South Africa; Cyanobacteria -- Geographical distribution; Prokaryotes -- South Africa; Mexilhao mussel -- South Africa; Mytilus galloprovincialis -- South Africa; Coastal biology -- South Africa; Coastal ecology -- South Africa; Mussels -- Geographical distribution; Mussels -- Predators of; Mussels -- Mortality -- South Africa; Mussels -- Ecology -- South Africa; Mussels -- Growth -- South Africa; Mussels -- Fertility -- South Africa